USE OF PLACENTAL DERIVATIVES IN THE TREATMENT OF BURNS (CIPEEX, 2025)
INTRODUCTION: Placental derivatives, including mesenchymal stem cells and amniotic membranes, have emerged as potential therapeutic agents in the treatment of burns. Due to their regenerative and anti-inflammatory properties, these derivatives can accelerate healing and improve clinical outcomes in patients with burns of varying degrees. OBJECTIVE: This study aims to analyze the use of placental derivatives in the treatment of burns, evaluating their effectiveness and safety in promoting tissue healing and regeneration. METHOD: To compose this integrative literature review, articles were obtained through searches in virtual databases (PubMed, SciELO, and Google Scholar), using the Health Sciences Descriptors (DeCS) "Burns," "Placental Derivatives," and "Tissue Regeneration" from 2018 to 2022. RESULTS: The use of placental derivatives in the treatment of burns has shown promising results, such as faster healing and reduced post-burn complications, including infections and hypertrophic scar formation. Studies like those by Koh et al. (2019) and Mahgoub et al. (2018) highlight that mesenchymal stem cells derived from the placenta promote angiogenesis and mitigate inflammation, accelerating tissue recovery. The amniotic membrane, as described by Shanmugam et al. (2020), has also proven effective in wound management, providing a protective barrier and support for regeneration. CONCLUSION: Although further studies are needed to confirm and standardize the use of placental derivatives in burn treatment, the preliminary evidence is encouraging. The use of these derivatives may represent a significant advance in regenerative medicine, offering an effective and safe approach to accelerating recovery in burn patients.
Keywords: burns; placental derivatives; tissue regeneration